Analisis Brand Image Universitas Andalas terhadap Pemilihan Kampus Tujuan PMM Inbound Angkatan 4 - Nurcinta Leoni; Budi Santoso (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study explores the brand image of Universitas Andalas through the lens of inbound students participating in the Pertukaran Mahasiswa Merdeka Batch 4 program. Using a qualitative method with a constructivist paradigm and descriptive approach, data were gathered from in-depth interviews with ten students from various Indonesian provinces. Findings reveal that Universitas Andalas developed a positive brand image across five dimensions of Aaker’s theory: brand awareness, brand association, perceived quality, brand loyalty, and supporting factors. The brand image was shaped not only by pre-arrival information but also by academic, cultural, and social experiences during the program. Students described the campus as emotionally engaging and worth recommending. Some participants, however, noted areas for improvement, including internal communication and information systems. This study concludes that brand image in higher education is influenced more by personal experiences than by reputation alone, offering valuable insights for educational branding and student exchange program development.